Acute uveitis: A rare adverse effect of miltefosine in the treatment of post-kala-azar dermal leishmaniasis - Pandey, Krishna (Rev Soc Bras Med Trop, 2020)
Post-kala-azar dermal leishmaniasis is a skin disorder occurring in 5-10% of visceral leishmaniasis patients after treatment with miltefosine,the first-line drug for this skin disorder. We reported a case of acute anterior uveitis,a rare adverse effect, experienced by a patient treated with miltefosine for post-kala-azar dermal leishmaniasis. This adverse effect developed after 15 days of miltefosine consumption, and the patient himself discontinued the treatment. The ophthalmic complication was completely resolved with antibiotics and steroid eye drops. After recovery from the ophthalmic complication, the patient was successfully treated with liposomal amphotericin B for the skin lesions.